2023
DOI: 10.1039/d2na00694d
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of mini gold nanorods: intersection with extracellular vesicles

Abstract: It is well-known that there are size- and shape-dependencies to nanoparticle uptake and processing by living cells. Small gold nanorods have shown to exhibit low toxicity and high clearance rates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Due to their size- and shape-dependent optical properties, gold nanoparticles (AuNPs) have drawn increasing interest for their potential use in biomedical applications; AuNPs are being studied for use as therapeutics, imaging agents, drug delivery systems, and diagnostics. However, the impact of introducing AuNPs into biological systems has yet to be fully characterized . Numerous studies have examined how altering various properties of AuNPs such as charge, surface chemistry, shape, and size affect AuNP-cell interactions. Previous work has shown that cellular uptake during chronic, long-term AuNP exposure is largely dependent on AuNP surface chemistry; moreover, surface chemistry-dependent changes in gene expression were observed following acute, low-dose AuNP exposure, highlighting the impact of AuNP surface chemistry on the biological response . Similarly, further studies have shown that changing AuNP surface functionalization alters the adsorption of serum proteins to the AuNP surface, which subsequently impacts interactions with cell membranes. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their size- and shape-dependent optical properties, gold nanoparticles (AuNPs) have drawn increasing interest for their potential use in biomedical applications; AuNPs are being studied for use as therapeutics, imaging agents, drug delivery systems, and diagnostics. However, the impact of introducing AuNPs into biological systems has yet to be fully characterized . Numerous studies have examined how altering various properties of AuNPs such as charge, surface chemistry, shape, and size affect AuNP-cell interactions. Previous work has shown that cellular uptake during chronic, long-term AuNP exposure is largely dependent on AuNP surface chemistry; moreover, surface chemistry-dependent changes in gene expression were observed following acute, low-dose AuNP exposure, highlighting the impact of AuNP surface chemistry on the biological response . Similarly, further studies have shown that changing AuNP surface functionalization alters the adsorption of serum proteins to the AuNP surface, which subsequently impacts interactions with cell membranes. …”
mentioning
confidence: 99%
“… 12 Numerous studies have examined how altering various properties of AuNPs such as charge, surface chemistry, shape, and size affect AuNP-cell interactions. 13 21 Previous work has shown that cellular uptake during chronic, long-term AuNP exposure is largely dependent on AuNP surface chemistry; moreover, surface chemistry-dependent changes in gene expression were observed following acute, low-dose AuNP exposure, highlighting the impact of AuNP surface chemistry on the biological response. 20 Similarly, further studies have shown that changing AuNP surface functionalization alters the adsorption of serum proteins to the AuNP surface, which subsequently impacts interactions with cell membranes.…”
mentioning
confidence: 99%